Analisis Perancangan Ulang Tata Letak Fasilitas Produksi Pada Kelompok Kerja Sub Assy Side Up Untuk Meminimasi Biaya Material Handling (Studi Kasus: PT. Yamaha Indonesia) - Fauzan Fadillah; Muhamad Naufal (Amal Insani Foundation, 2022)
Layout design is one of the important factors for the continuity of production activities. Layout is very important and interrelated with other facilities to support the smooth running of production activities. A good and optimal facility layout can reduce production costs, increase efficiency and productivity. This research was carried out in the UP subassy side working group, PT. Yamaha Indonesia which is a company that manufactures pianos. The problem that exists in the UP sub assembly work group is that the existing layout is not optimal as evidenced by the existence of a separate work area and a different building from the work group. Because the distance is far and the building is different, the operator becomes idle because they have to wait for the cabinet to be sent. The purpose of this research is to obtain an optimal and efficient layout of production facilities so as to minimize material handling costs and increase productivity using the SLP and Blocplan methods. The results of this study indicate that there is a significant difference in the total distance between facilities from the initial layout, the proposed layout using the SLP method shows a total distance between facilities of 960.2 m with an efficiency of 95.5% and the Blocplan method shows a total distance of 1,118.6 m with an efficiency of 94.8% . So it can be concluded that the design results of the SLP method are efficient proposed layouts.